Targeted high volume hemofiltration could avoid extracorporeal membrane oxygenation in some patients with severe Hantavirus cardiopulmonary syndrome. Issue 8 (23rd March 2021) - López, René; Pérez‐Araos, Rodrigo; Salazar, Álvaro; Espinoza, Mauricio; Vial, Cecilia; Cuiza, Analia; Vial, Pablo A.; Graf, Jerónimo
Abstract: Background: Hantavirus cardiopulmonary syndrome (HCPS) has a high lethality. Severe cases may be rescued by venoarterial extracorporeal membrane oxygenation (VA ECMO), alongside substantial complications. High volume hemofiltration (HVHF) is a depurative technique that provides homeostatic balance allowing hemodynamic stabilization in some critically ill patients. Methods: We implemented HVHF before VA ECMO consideration in the last five severe HCPS patients requiring mechanical ventilation and vasoactive drugs admitted to our intensive care unit. Patients were considered HVHF‐responders if VA ECMO was avoided and HVHF‐nonresponders if VA ECMO support was needed despite HVHF. A targeted‐HVHF strategy compounded by aggressive hyperoncotic albumin, sodium bicarbonate, and calcium supplementation plus ultrafiltration to avoid fluid overload was implemented on three patients. Results: Patients had maximum serum lactate of 8.8 (8.7–12.8) mmol/L and a lowest cardiac index of 1.8 (1.8–1.9) L/min/m 2 . The first two required VA ECMO. They were connected later to HVHF, displayed progressive tachycardia and declining stroke volume. The opposite was true for HVHF‐responders who received targeted‐HVHF. All patients survived, but one of the VA ECMO patients suffered a vascular complication. Conclusion: HVHF may contribute to support severe HCPS patients avoiding the need for VA ECMO in some. Early connection and targeted‐HVHF may increase the chance of success.